Accessible Museums - Keskinova, Angelka; Troshanska, Jasmina; Ramadani Rasmini, Teuta; Georgievski, Petar (Turistika Skopje, 2021)
Republic of Macedonia has been working on an inclusive policy and accessible society for decades, but most often, we associate this term with educational processes and institutions. The social part of integrated rehabilitation, which includes culture, remains in the shadows and is usually in the background when creating an inclusive society. The purpose of our research was to determine how accessible museums in the Republic of Macedonia are for people with disabilities, specifically for people with autism spectrum disorders (ASD). In this regard, we surveyed 39 families of children with ASD, and 112 families of children with typical development as a control group. Possibility of cultural development during the COVID 19 pandemic additionally was analyzed. According to the results, both groups of respondents rarely visit museums (usually once a year), and as a reason for the rare visits they cite that contents are not adapted for the needs of their children. The results of the research indicate the need to expand the concept of an inclusive society and adaptation of the content to the needs of people with ASD.
Keywords: Accessible museums, Autism spectrum disorders, families